DIREITO PENAL DO AUTOR: os maus antecedentes à luz da tese de repercussão geral 150 - VIEIRA, Rayane Duarte (2023)
The present work analyzes the Extraordinary Appeal 593.818 dated 17/08/2020 that gave rise to the thesis of General Repercussion nº 150 in which it was discussed, in the light of art. 5, LVII, of the Federal Constitution, the possibility, or not, of convictions that became final and unappealable for more than five years being considered as bad antecedents for the purpose of fixing the base penalty, originating the following thesis: “It does not apply for the recognition of the bad antecedents the five-year period of prescription of the recidivism, foreseen in the art. 64, I, of the Penal Code”. With regard to the methodology used, an inductive method was used, with a case study as a procedural method, of the legal-descriptive type, with a research, bibliographical and documental technique. Initially, the origin of the penalties and their introduction in the Brazilian legal system were analyzed, relating to the constitutional principles of the penalty, in order to enable the understanding of the insertion of the use of bad antecedents in the Penal Code of 1940, as a judicial circumstance for the purpose of aggravation base feather in the first phase of feather dosimetry. Then, the evolution of doctrine and jurisprudence was analyzed in relation to the use of bad antecedents and adoption of the criminal law of the fact in the dosimetry of the penalty to the detriment of the criminal law of the author. In the end, the General Repercussion Thesis 150 and its use in the Court of Justice of the State of Maranhão were analyzed, as well as the impacts of the decision for the resocialization of the convict as well as the right to be forgotten in the criminal sphere. As a general objective, the present study aimed to analyze to what extent the perpetuity in the use of bad antecedents in the judgments of the STF, STJ and TJ/MA as the cause of the increase in the base penalty goes against the Author's Criminal Law Theory and offends to CF/1988, from 2020. In a preliminary hypothesis, it was noted the subjectivation of Criminal Law in Brazilian jurisprudence by the aggravation of the penalty for bad antecedents, at any time, aligning with the Theory of Criminal Law of the Author, to the detriment of the Theory of the Criminal Law of the Fact. After the research carried out, the automatic use of bad antecedents in the processes judged by the TJ/MA was verified, contrary to what was sedimented in the General Repercussion 150 thesis. general repercussion 150 is not applied in a manner compatible with the precepts established in the thesis, and consequently in disagreement with the constitutional principles of human dignity, presumption of innocence and individualization of the penalty.